2014
DOI: 10.1007/s12017-014-8319-5
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation of Blood in Schizophrenia by Adjusting for Estimated Cellular Proportions

Abstract: DNA methylation, which is the transference of a methyl group to the 5'-carbon position of the cytosine in a CpG dinucleotide, is one of the major mechanisms of epigenetic modifications. A number of studies have demonstrated altered DNA methylation of peripheral blood cells in schizophrenia (SCZ) in previous studies. However, most of these studies have been limited to the analysis of the CpG sites in CpG islands in gene promoter regions, and cell-type proportions of peripheral leukocytes, which may be one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 58 publications
4
19
0
Order By: Relevance
“…The proportion of CpG sites with decreased DNA methylation was higher than the proportion of sites with increased DNA methylation after clozapine treatment (55.2% vs. 44.8%, respectively). Consistent with this finding, we previously demonstrated that DNA hyper-methylation patterns frequently occurred in medication-free patients with SCZ, while hypo-methylation was more common in patients with SCZ treated with antipsychotics [12,14]. We also found that decreased DNA methylation following clozapine treatment was more likely to occur at CpG sites located in CGIs in gene promoter regions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The proportion of CpG sites with decreased DNA methylation was higher than the proportion of sites with increased DNA methylation after clozapine treatment (55.2% vs. 44.8%, respectively). Consistent with this finding, we previously demonstrated that DNA hyper-methylation patterns frequently occurred in medication-free patients with SCZ, while hypo-methylation was more common in patients with SCZ treated with antipsychotics [12,14]. We also found that decreased DNA methylation following clozapine treatment was more likely to occur at CpG sites located in CGIs in gene promoter regions.…”
Section: Discussionsupporting
confidence: 83%
“…DNA methylation mainly occurs at the 5′ position of the cytosine base followed by a guanine base that is called CpG [9]. A number of studies have demonstrated aberrant DNA methylation in SCZ [10,11,12,13,14,15,16,17,18]. Furthermore, growing evidence suggests that DNA methylation may be involved in the therapeutic efficacy of atypical antipsychotic drugs [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic nature of epigenetic processes means that unlike in genetic epidemiology a range of potentially important confounding factors need to be considered, including tissue or cell type, age, sex, lifestyle exposures, and reverse causation [9]. In recent years there has been a growing interest in the role of developmentally regulated epigenetic variation in the molecular etiology of schizophrenia, supported by data from recent analyses of DNA methylation in co-twins from disease-discordant monozygotic twin pairs [12], clinical sample cohorts [13, 14], and post-mortem brain tissue [15–17]. …”
Section: Introductionmentioning
confidence: 99%
“…Global DNA Global hypomethylation [70] 100/100 Peripheral blood cells BDNF Hypermethylation in BDNF promoter I [71] 24/24 Brain tissue Genome-wide DNA methylation analysis Significant differences in DNA methylation at multiple loci [72] 35/35 Frontal cortex CpG genome-wide islands Significant differences in DNA methylation at multiple loci [73] 14/14 Prefrontal cortex GAD1 Hypermethylation [74] 63/42 Peripheral blood leukocytes Genome-wide DNA methylation analysis Significant differences in DNA methylation at multiple loci [75] 61/38 Peripheral blood LRRTM1 Hypomethylation in LRRTM1 promoter [76] 80/71 Peripheral blood DRD2 DRD4 DRD5…”
Section: Articlementioning
confidence: 99%